Rasgos biológicos y poblacionales del depredador ceraeochrysa sp. nr. cincta (México) (neuroptera: chrysopidae) - Ramírez-Delgado, Manuel; López-Arroyo, J. Isabel; González-Hernández, Alejandro; Badii-Zabeh, Mohammad H. (Instituto de Ecología, A.C., 2007)
Ceraeochrysa sp. nr. cincta (Mexico) (Neuroptera: Chrysopidae) is a predator with cryptic larvae that attack diverse arthropod pests in fruit trees of Mexico. In order to contribute to facilitate the possible use of this beneficial insect in pest biological control, the objective of this study was to determine lifehistory traits and population parameters. We studied under controlled lab conditions three cohorts of 50 C. sp. nr. cincta specimens. The results showed that the species completed development, from egg to adult emergence, in 29 days, with 96% survivorship. The demographic statistics were: Ro = 95, T = 9 days, Td = 8 days and rm = 0.081 females per female per day. These traits are similar to some indicated for other reported chrysopid species; in contrast, C. sp. nr. cincta (Mexico) had a long preoviposition period, small proportion of ovipositing females and reduced egg fertility. Such reproductive characters were studied in a subsequent experiment, where females were maintained under different male ratios (1:0, 1:1, 1:2, 1:3 and 1:5). Except for the females that were kept without presence of males (1:0), those that were maintained temporarily with 1, 2, 3, and 5 males had short preoviposition period, as well as high values of ovipositing females, egg fertility and fecundity. The number of matings under the different proportions of female:male were not significantly different. The biological traits and demographic statistics results show the potential for mass-rearing and use of the predator in pest biological control in Mexico.